The Topos of Ragnarök in the Utopian Thought of William Morris - SPINOZZI, Paola (Universitätsverlag Winter, 2011)
The reasons why not only William Morris, but also George Webbe Dasent, Thomas Carlyle, Samuel Laing, Matthew Arnold, Charles Kingsley, Edmund Gosse, Henry Wadsworth Longfellow and James Russell Lowell all read, translated and rewrote Old Norse literature are large-scale, encompassing the history of European culture, politics, ethics, literature and comparative philology. They studied and visited Iceland in order to retrace the cultural origins of Northern Europe, to consolidate their ideological views about social and political institutions, to present the heroic code of behaviour as an ideal ethical model for the Victorians, to revive Old Norse narratives and to find a language which could express their pathos. Old Norse history and literature were perceived and valued as models for the cultural identity of Northern Europe during the nation-building process in the nineteenth century. Owing to their geographical isolation, Nordic countries had been able to preserve their Germanic matrix. The quest for the origins of Germanic culture in Northern Europe was thus accomplished by assigning a prominent status to Iceland. The originality and distinctiveness of the peoples which settled there is emphasised by Morris and Eiríkr Magnússon in the Preface to the first volume of The Saga Library published in 1891. For Morris ancient Iceland had been able to develop its forms of government and culture owing to the absence of Roman and then Norman feudalism and to develop a form of proto-socialism founded on the concept of kinship. Morris’s knowledge of the history of Europe was based on the study of The Decline and Fall of the Roman Empire (1776) by Edward Gibbon in the 1852 edition annotated by H. H. Milman and of A History of the Fall of the Roman Empire (1834) by J. C. L. Sismondi. The Victorian reception of the ethos personified by the saga-heroes entailed philosophical and anthropological interrogations. The acquaintance with Old Norse gods and goddesses, forceful women and warriors, would invite readers to reflect on, ...